Thiolated graphene - a new platform for anchoring CdSe quantum dots for hybrid heterostructures - Debgupta, Joyashish; Pillai, Vijayamohanan K. (Nanoscale, 2013)
Effective organization of small CdSe quantum dots on graphene sheets has been achieved by a simple solution exchange with thiol terminated graphene prepared by diazonium salt chemistry. This generic methodology of CdSe QD attachment to any graphene surface has remarkable implications in designing hybrid heterostructures.